Mycotoxins in Florida Pastures - Marcelo O. Wallau; Brittany L. Justesen; Ann R. Soffes Blount; Luiz Ferraretto; Glen Aiken; Aaron Stam (EDIS)
Beef cattle producers in Florida have expressed concerns about the potential presence of mycotoxins in summer perennial forages. In other regions of the US, mycotoxins in forage crops have caused productivity and economic losses. This 3-page fact sheet provides information about the current state of knowledge regarding mycotoxins in Florida perennial grass pastures. Written by Marcelo Wallau, Brittany Justesen, Ann Blount, Luiz Ferraretto, Glen Aiken, and Aaron Stam, and published by the UF/IFAS Agronomy Department, August 2018. http://edis.ifas.ufl.edu/ag422